Thiol/disulfide homeostasis as a marker of oxidative stress in rosacea: a controlled spectrophotometric study. (2nd January 2019) - Sener, Sertac; Akbas, Ayse; Kilinc, Fadime; Baran, Pervin; Erel, Ozcan; Aktas, Akin
Abstract: Background: Rosacea is the chronic inflammatory disease of the facial skin. Although its aetiology is not clear yet, inflammatory processes triggered by oxidative stress and oxidation of lipids have been suggested to play a role. While studies on the relationship between inflammation and oxidative stress are ongoing, thiol metabolism and its role in oxidative stress have also begun to be investigated. Thiols are among the key molecules of protein metabolism in the organism and they are the firstly consumed antioxidants in case of oxidative stress. Thiols regulate intracellular redox metabolism and protect keratinocytes against the results of oxidative alterations in the stratum corneum. There is a balance known as dynamic thiol/disulfide homeostasis between thiols and their oxidized forms; disulfides. Aim: This study aimed to determine the effects of oxidative stress on protein metabolism in rosacea patients by investigating thiol/disulfide homeostasis using a newly developed and fully automated method. Determination of plasma thiol levels provides important clues regarding the extent of free radical-mediated oxidation of proteins causing damage in rosacea. Methods: The study included 50 rosacea patients who were diagnosed clinically or histopathologically with rosacea and 42 age- and gender-matched healthy controls. Plasma levels of native thiol, total thiol, and disulfide were determined. The following ratios were calculated: disulfide/native thiol ratio, disulfide/total thiol ratio, and native thiol/total thiol ratio. Results: The mean age was 41.8 ± 10.5 in the rosacea patients (35 females) and 42.5 ± 10.3 years in the control group (33 females). The mean disulfide level was found to be significantly higher in the rosacea patients than in the control group (23.4 ± 5.5 µM/L and 17.3 ± 6.2µM/L, respectively; p < 0.001). The mean disulfide/native thiol ratio (0.055 ± 0.016 vs. 0.041 ± 0.017) and the mean disulfide/total thiol ratio (0.049 ± 0.012 vs.0.037 ± 0.013) were significantly higher and the mean native thiol/total thiol ratio (0.884 ± 0.118 vs. 0.923 ± 0.027) was significantly lower in the patients as compared with the controls ( p < 0.05 for all). Conclusion: In rosacea patients, the thiol/disulfide balance was observed to shift towards disulfides, which could be considered an indicator of oxidative stress in rosacea.